Problematika Kompetensi Pedagogik Guru dalam Pembelajaran - Sele, Yunawati; Sila, Vinsensia Ulia Rita (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
The teacher is a party that has great responsibility in achieving learning goals. One of the competencies that must be possessed by teachers is pedagogical competence. This research was conducted with the aim of uncovering the problems of teacher pedagogical competence in learning, as well as alternative solutions that can be done to overcome these problems. The method used in this research is literature analysis. The literature is a scientific article that discusses the problems of teacher pedagogical competence. The results of the study show that the problem of teacher pedagogic competence is the lack of the teacher's ability to plan, implement and evaluate the learning that is carried out. Planning, implementation and evaluation are related to all aspects of learning, be it objectives, materials, methods or evaluation. Alternative solutions that can be implemented are increasing teacher awareness of the importance of self-motivation, maximizing the function of the LPTK (Educational Personnel Providing Institution) in preparing competent teacher candidates and maximizing the function of teacher competency development programs.